A missionariedade da Igreja na Diocese de Coari - Gordiano, Raimundo Carvalho (2017)
The Church has its origin, source and fullness in Trinitarian pericorese. The inner movement of divine communion is overflowing with life. The Church is involved in the creative and saving mission of God. This ecclesiological perspective was deepened and assumed in the Second Vatican Council. This research portrays a reading of the missionary nature of the Church in the Diocese of Coari. It points out three facets taken over and built during its fifty years of evangelization: ecclesiology, sociopastoral action and missionary life as evangelizing and pastoral reflection. The primary sources are the Dogmatic Constitution Lumen Gentium, the Pastoral Constitution Gaudium et Spes and the Ad Gentes Decree. The bibliographical sources, the texts of the Magisterium and the Tradition are based and help to indicate the perspectives of the mission of the Local Church and its inspirations for the communion of the People of God. The diocese is missionary and continues its construction. You always need to update your evangelizing action. Installed in the ambience of the traditional Amazonian culture, the presence of urban culture has a strong presence. Diocesanism invites us to think and update our mission in order to renew ourselves permanently as a Missionary Church